Discovering disciplinary differences: blending data sources to explore the student online behaviors in a University English course. Issue 2 (20th May 2019) - Foung, Dennis; Chen, Julia
Abstract : Purpose: This study aims to explore disciplinary differences in completing blended learning tasks in an academic literacy course and the feasibility of adopting a blended learning analytics approach to explore disciplinary differences. Design/methodology/approach: Following a learning analytics approach, this study blends data from the learning management system and timetabling arrangements. Findings: Results suggest that online behaviors of design students and accounting students are different in terms of starting day and completion rate. Blending data sources also provides a new perspective to our learning analytics study. Originality/value: This study is an important contribution to the field because studies on learning analytics with multiple data sources are rare, and most disciplinary studies rely on survey data; students' actual behaviors are under-explored.